2013
DOI: 10.1080/10962247.2013.832713
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of air emissions associated with shale gas development and production in the Barnett Shale

Abstract: Information regarding air emissions from shale gas development and production is critically important given production is now occurring in highly urbanized areas across the United States. Methane, the primary shale gas constituent, contributes substantially to climate change; other natural gas constituents are known to have adverse health effects. This study goes beyond previous Barnett Shale field studies by encompassing a wider variety of production equipment (wells, tanks, compressors, and separators) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 12 publications
0
40
1
Order By: Relevance
“…Our study differs from the TCEQ (2010), Zielinska et al (2010), and Rich et al (2014) studies in that our study includes a larger number of sites, but is more limited in terms of compounds analyzed. As a mobile measurement survey, our study emphasized geographic breadth of measurement.…”
Section: Study Objectives and Scopecontrasting
confidence: 40%
See 2 more Smart Citations
“…Our study differs from the TCEQ (2010), Zielinska et al (2010), and Rich et al (2014) studies in that our study includes a larger number of sites, but is more limited in terms of compounds analyzed. As a mobile measurement survey, our study emphasized geographic breadth of measurement.…”
Section: Study Objectives and Scopecontrasting
confidence: 40%
“…In the Barnett Shale, ambient measurement studies of air pollutants associated with natural gas drilling and production have been conducted by the Texas Commission on Environmental Quality (2010), Zielinska et al (2010), and Rich et al (2014). In response to public complaints and health concerns, the TCEQ conducted ambient air quality monitoring of VOCs and reduced sulfides in Denton, Wise, Parker, Hood, Johnson, and Tarrant counties in three phases during August, October, andNovember 2009 (TCEQ, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent research has shown increased air pollution in areas close to shale gas extraction and processing infrastructure (e.g., Litovitz et al, 2013;Rich et al, 2014). Increased air pollution associated with shale gas development may have significant public health implications (e.g., McKenzie et al, 2012).…”
Section: Costsmentioning
confidence: 99%
“…Emissions of VOC, CO, NO x , and ultrafine PM have been reported from several stages of the shale gas production sector (i.e. active well pads, compressor stations, and processing facilities) (Goetz et al, 2015;Pekney et al, 2014;Rich et al, 2014;Warneke et al, 2014).…”
mentioning
confidence: 99%